Hybrid anisotropic nanostructures for dual-modal cancer imaging and image-guided chemo-thermo therapies. (October 2016) - Zhang, Ruiping; Cheng, Kai; Antaris, Alexander L.; Ma, Xiaowei; Yang, Min; Ramakrishnan, Sindhuja; Liu, Guifeng; Lu, Alex; Dai, Hongjie; Tian, Mei; Cheng, Zhen
Abstract: The multimodality theranostic system, which can integrate two or more different therapeutic modalities and multimodal imaging agents into a nanoentity, shows great promising prospects for the cancer treatment. Herein, we developed an efficient and novel strategy to synthesize hybrid anisotropic nanoparticles (HANs) with intrinsic multimodal theranostic capability [chemotherapy, photothermal therapy, magnetic resonance imaging (MRI), and photoacoustic imaging (PAI)]. For the first time, under the guidance of MRI and PAI, the chemotherapy and thermotherapy induced by administration of multifunctional hybrid nanoprobes were applied simultaneously to the treatment of colon cancer-bearing mice in vivo .